Meta-analysis and publication bias: How well does the FAT-PET-PEESE procedure work? A reply to Hong (International Journal for Re-Views in Empirical Economics, 2019) - W. Robert Reed (International Journal for Re-Views in Empirical Economics (IREE), 2019)
In this article Robert W. Reed replies to Hong's replication study published earlier this year (IREE, 2019-4).
https://doi.org/10.15456/iree.2018280.233725; https://doi.org/10.7910/DVN/4IOLOP
Keywords: B41; C15; C18; 330; Meta-Analysis; Publication Bias; Funnel Asymmetry Test (FAT); Precision Effect Estimate with Standard Error (PEESE); Monte Carlo Simulations; Replication Study